DIGITAL EDUCATION: OPPORTUNITIES, THREATS, AND CHALLENGES - Bilkisu Gambo Danmuchikwali; Muhammmad Muhammad Suleiman (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2020)
Digital education is largely an innovation of the last few decades, although it already existed in various forms slightly earlier. Shortly, the educational system environments are anticipated as mitigation to unforeseen natural and artificial pandemics such as Covid-19 in 2020 by the significant changes associated with the digitalization of some portion of the system. This article aims to provide valuable perspectives of ICT and digital education into its future benefits, risks, and challenges of embracing the latest technologies in the digital era, and vast online open courses. We have checked a profound change in the way we interact and generate within the academics with the advent of internet technologies. Globally, the digital revolution favoured open access to information. Classrooms today have a lot of ICT resources nearly all the teachers have made great strides to incorporate digital technology to increase access to information and collaborative activities for the learners.